J. W. Valvasor and J. Rabatta on the Croatian Military Border in 1689 and 1719. Stereotypes and mentality in the Triple Frontier comparative perspectives - Lazanin, Sanja (Array, 1998)
In microhistorical research of the triple frontier 'history from below' is so closely intermeshed with 'history from above' that it is of especial importance to study the 'meeting' between people of most varied backgrounds, often to observe how those in positions of high command come into contact with ordinary people and with the reality of the triple frontier itself. Written sources which tell us about these experiences are important for an ego/history, i. e. for one's 'image of oneself', as the product of interaction with the environment of the triple frontier, and also from the point of view of the 'image of others' in their presentation of mentality, or of stereotypes etc. This work is an attempt to use archival material and a work of literature as a source for comparative historical research in both ego-history and history of the 'image of others'.